2001
DOI: 10.1590/s0102-311x2001000500023
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of human and canine visceral leishmaniasis in Belo Horizonte, Minas Gerais State, Brasil, 1994-1997

Abstract: In this paper, we present spatial analysis of the association between all incidents cases of human Visceral Leishmaniasis and seropositive dogs, from 1994 to 1997

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
69
1
22

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 7 publications
3
69
1
22
Order By: Relevance
“…A presença de 50 a 70% de cães assintomáticos em áreas endêmicas, potencialmente infectantes para o vetor 12 , denota a importância dos inquéritos sorológicos caninos para que se antecipem as ações profiláticas, já que os casos caninos precedem a doença no homem 18 . Nesta investigação, a porcentagem obtida de cães assintomáticos foi de 56,2%, não divergindo do cenário encontrado no país.…”
Section: Discussionunclassified
“…A presença de 50 a 70% de cães assintomáticos em áreas endêmicas, potencialmente infectantes para o vetor 12 , denota a importância dos inquéritos sorológicos caninos para que se antecipem as ações profiláticas, já que os casos caninos precedem a doença no homem 18 . Nesta investigação, a porcentagem obtida de cães assintomáticos foi de 56,2%, não divergindo do cenário encontrado no país.…”
Section: Discussionunclassified
“…As a general rule, where transmission of L. infantum among humans occurs, it also occurs among dogs 19,23,50 . In one study, the highest prevalence of infection among dogs was not associated with the highest incidence among humans 51 , but in two other studies in Brazil and in a third in Iran, this association was shown [52][53][54] . These discordant results demonstrate that the association between human and canine infections is not strong and suggest that the infections between the two hosts may have distinct dynamics, with a more complex relationship than previously thought.…”
Section: The Importance Of Dog Infection For Human Kala-azarmentioning
confidence: 92%
“…Em 1992, foram diagnosticados cães positivos no município, e, em 1994, os primeiros casos humanos em áreas limítrofes do município de Sabará (Oliveira et al, 2001), onde um caso havia sido registrado em 1989 (Genaro et al, 1990). Inicialmente com característica focal (Oliveira et al, 2001), a LV tornou-se amplamente distribuída em todas as regionais, acometendo pessoas de condições socioeconômicas mais favoráveis e com aumento da ocorrência no grupo de adultos jovens (Lopes, 2009). O serviço público, apesar da intensificação das ações de controle, não conseguiu interromper a rápida expansão geográfica da doença e reduzir a incidência da LV, que conta com mais de cem casos anuais (Leishmaniose..., 2008).…”
unclassified